أحكام المرأة المطلقة بعد الدخول بين الشريعة والقانون الجزائري - بن عاشور, عبد المؤمن (University of Eloued-جامعة الوادي, 2021)
" موضوع البحث يتعلق بعنصر مهم في المجتمع الذي لا يقوم ولا يصلح إلا بصلاحه، ألا وهو المرأة، وهذا الجانب من الدراسة يتعلق بأحكام المرأة المطلقة بعد الدخول بين الشريعة الإسلامية وقانون الأسرة الجزائري. فقد حاول هذا البحث الإجابة على عدة إشكالات من أبرزها: إلى أي مدي وفق المشرع الجزائري في إحاطته بالأحكام المتعلقة بالمرأة المطلقة بعد الدخول مقارنة بالشريعة الإسلامية ؟ وتُوِّج البحث في ختامه ببعض النتائج والإقترحات منها: أن الأصل في الطلاق الإباحة ولأنه لا يباح إلا لحاجته وأياً ما كان الأمر في اختلاف الفقهاء حول الحظر والإباحة في الحكم الأصلي للطلاق فإنهم يتفقون أن الطلاق تحكمه الأحكام الخمسة. على الدولة الاهتمام بقانون الأسرة وإعادة النظر في بعض المواد التي لا تتطابق مع خصوصيات الفرد الجزائري ولا الشرع الحكيم. "The subject of the research relates to an important element in a society that is only valid and valid, namely women, and this aspect of the study relates to the provisions of divorced women after entering between Islamic law and Algerian family law. This research tried to answer several problems, the most prominent of which is: to what extent according to the Algerian legislator in informing him of the provisions concerning divorced women after entry compared to Islamic law? The research culminated in some findings and suggestions, including: that the origin of divorce is permissible and that it is permissible only for its need and whatever the difference in the jurisprudence about the prohibition and legalization in the original ruling of divorce, they agree that divorce is governed by the five provisions. The state should take care of family law and reconsider some articles that do not correspond to the specifics of the Algerian individual or the wise Sharia
مذكرة ماستر
Keywords: أحكام المرأة - الطلاق- المدخول بيها - الآثار المادية -الآثار الغيرمادية -القانون الجزائري -الشريعة الاسلامية; Women's rulings-divorce-income with it-physic- Intangible effects-al effects-Algerian law-Islamic law